Some Statistical Characteristics Depending on the Maximum Variance of Solution of Two Dimensional Stochastic Fredholm Integral Equation contains Two Gamma Processes - Mohammad W. Muflih; Noor A. A. Jabbar (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
In this paper, we find the two solutions of two dimensional stochastic Fredholm integral equations contain two gamma processes differ by the parameters in two cases and equal in the third are solved by the Adomain decomposition method. As a result of the solutions probability density functions and their variances at the time t are derived by depending upon the maximum variances of each probability density function with respect to the three cases. The auto covariance and the power spectral density functions are also derived. To indicate which of the three cases is the best, the auto correlation coefficients are calculated.